2011
DOI: 10.12659/msm.881377
|View full text |Cite
|
Sign up to set email alerts
|

The minimally-invasive thyroidectomy incision: A histological analysis

Abstract: SummaryBackgroundMinimally invasive thyroidectomy (MIT) has gained popularity in the surgical management of benign and malignant pathology of the thyroid. One of the main benefits of utilizing this technique is the use of smaller incisions resulting in increased cosmetic satisfaction. Unfortunately, the retraction required for adequate exposure during MIT may lead to skin damage, impaired wound healing and poor cosmetic outcomes. Some have proposed that excising incision edges prior to closure may improve cosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, the retraction required for adequate exposure and the augmented need for preparation from incision sites far from the neck (e.g., axilla or breast) during these procedures may lead to augmented skin and tissue damage. This can result in impaired wound healing and, in some cases, poor cosmetic results [28]. In a recent review, it was concluded that ''scarless'' (in the neck) endoscopic thyroid approaches via the axilla, anterior/breast, and a hybrid (anterior combined with axilla) comes at a steep price by being maximally invasive in other areas and involving longer operative times and greater postoperative pain [29].…”
Section: Body Image Questionnairementioning
confidence: 99%
“…Furthermore, the retraction required for adequate exposure and the augmented need for preparation from incision sites far from the neck (e.g., axilla or breast) during these procedures may lead to augmented skin and tissue damage. This can result in impaired wound healing and, in some cases, poor cosmetic results [28]. In a recent review, it was concluded that ''scarless'' (in the neck) endoscopic thyroid approaches via the axilla, anterior/breast, and a hybrid (anterior combined with axilla) comes at a steep price by being maximally invasive in other areas and involving longer operative times and greater postoperative pain [29].…”
Section: Body Image Questionnairementioning
confidence: 99%
“…However Perigli et al in their study did not find any difference in the postoperative pain, as well as in cosmetic result and hypoparathyroidism in the groups of MIVAT and MINET surgeries [ 23 ]. Furthermore no histological changes in structure of the scar were found when comparing specimens of different retraction forces [ 24 ].…”
Section: Discussionmentioning
confidence: 99%